Economic Contributions of Florida's Agricultural, Natural Resource, Food and Kindred Product Manufacturing and Distribution, and Service Industries in 2008 - Alan W. Hodges; Mohammad Rahmani (EDIS, 2010)
FE829, a 21-page illustrated report by Alan W. Hodges and Mohammad Rahmani, provides estimates of these industries’ economic contributions to Florida in 2008. Published by the UF Department of Food and Resource Economics, February 2010.